Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Dengan Pendekatan Weighted Product (Studi Kasus Pada PT Republika Media Mandiri Jakarta) - Saraswati, Sandra Dewi (STMIK Budi Darma, 2019)
Assessment of employee performance in a company is very important, the purpose is to evaluate employee performance so that performance in the company increases. Therefore, we need a system that can help companies to process the results of employee performance assessment, by using the Decision Support System with Weighted Product Method. Weigthted Product is a settlement method by using multiplication to connect the attribute value, where the value must be raised first with the weight of the attribute in question. By using the Weighted Product method, it is expected that the best volunteer selection process is more effective and efficient so that managers quickly get the results of the assessment in accordance with the assessment of each employee